BAKTI SOSIAL DENGAN MEMBANGUN KARAKTER SISWA DALAM MENJAGA KEBERSIHAN LINGKUNGAN SEJAK DINI - Eni Setianingsih; Jihan Arlitania Utami; Klarita Novela Wenda; Klansina J.N Korisano; Jhosua Frans Rumbarar (Adiba Aisha Amira, 2025)
A Community Service Activity (PKM) themed ‘Social Service by Building Student Character in Maintaining Environmental Cleanliness from an Early Age’ was held at SD Inpres Timika IX with the aim of increasing student awareness of the importance of environmental cleanliness while instilling values of character, togetherness, and nationalism. The methods used included socialisation, community service, creative competitions to celebrate Independence Day, and educational outreach. The results of the activity showed an increase in students' concern for school cleanliness, the formation of social solidarity between students, teachers, and pupils, and the strengthening of national values through independence-themed competitions. The main obstacle faced was the limited availability of sanitation facilities, necessitating continued support to ensure the sustainability of this programme. Overall, this PKM activity successfully achieved its objectives and provided tangible benefits to the school and the surrounding community.